The tragedy of Hamlet, Prince of Denmark - Shakespeare, William, 1564-1616; Mowat, Barbara A; Werstine, Paul; Folger Shakespeare Library (2012)
This edition includes freshly edited text based on the best early printed version of the play, with full explanatory notes, scene-by-scene plot summaries, and a key to famous lines and passages that make the Bard come to life for all readers
Machine generated contents note: The Tragedy of Hamlet, Prince of Denmark Text of the Play with Commentary
Includes bibliographical references (pages 339-369)
Keywords: Shakespeare, William, -- 1564-1616.; Hamlet -- (Legendary character) -- Drama; Kings and rulers -- Succession -- Drama; Murder victims' families -- Drama; Fathers -- Death -- Drama; Revenge -- Drama; Princes -- Drama; Denmark -- Drama